1998
DOI: 10.1095/biolreprod59.4.807
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Inhibin/Activin Subunit, Activin Receptor, and Follistatin Messenger Ribonucleic Acid in Human and Mouse Oocytes: Evidence for Activin's Paracrine Signaling from Granulosa Cells to Oocytes1

Abstract: Inhibin, activin, and follistatin (FS) are gonadal proteins that appear to have a role in regulating folliculogenesis through possible paracrine and/or autocrine interactions. To further examine the potential role of activin in oocyte-granulosa cell communication, we developed a sensitive reverse transcription-polymerase chain reaction protocol to analyze mRNA for the alpha, betaA, and betaB inhibin/activin subunits, FS, and the four activin receptor subtypes in individual human and mouse oocytes. The resultin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
52
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(59 citation statements)
references
References 41 publications
(47 reference statements)
6
52
1
Order By: Relevance
“…Gonadal inhibins and activins were first described as regulators of pituitary function, specifically for the regulation of FSH␤ expression (46 -49). Activin receptors (whose activities are possibly blocked by inhibins) have been found on oocytes (50). It is possible that these peptides may regulate oocyte development by modulating the expression and production of ovarian FSH␤ and LH␤.…”
Section: Discussionmentioning
confidence: 99%
“…Gonadal inhibins and activins were first described as regulators of pituitary function, specifically for the regulation of FSH␤ expression (46 -49). Activin receptors (whose activities are possibly blocked by inhibins) have been found on oocytes (50). It is possible that these peptides may regulate oocyte development by modulating the expression and production of ovarian FSH␤ and LH␤.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been suggested that early mouse and human embryos, from the four-cell stage to the morula stage, are unable to synthesize activins, as no mRNA for these proteins has been identified at these stages of development (Lu et al 1993, He et al 1999. Furthermore, it has been proposed that activin, which binds to the activin type I and type II receptors on the preimplantation embryo, may be derived from the surrounding tissue such as the endosalpinx (He et al 1999), and that the oocyte is capable of receiving an activin signal produced by surrounding cumulus cells, but not of transmitting one (Sidis et al 1998). Moreover, it has been suggested that activin has a local paracrine or autocrine role with regard to early embryonic development as it is co-expressed with follistatin, the binding protein of activin, which would mitigate against tubal activin having a more distant site of action (Bahathiq et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Cumulus granulosa cells surrounding the oocyte express inhibin/activin subunits (a, bA, bB) and follistatin (Roberts et al 1993, Sidis et al 1998, Izadyar et al 1998, Silva et al 2003, and the oocyte expresses both type-I and type-II activin receptors (Cameron et al 1994, Izadyar et al 1998, Sidis et al 1998. In both rodents and primates, activin A accelerates oocyte maturation (Sadatsuki et al 1993, Alak et al 1996 and in the bovine, oocyte developmental competence is improved (Silva & Knight 1998).…”
Section: Inhibin-activin Systemmentioning
confidence: 99%